Common Kilka Hydrolysis: Investigation of Functional and In Vitro Antioxidant Properties of Hydrolysates Obtained by Kiwifruit and Ginger Proteases. Issue 3 (16th March 2018) - Hemmati, Vahid; Jamshidian, Majid; Safari, Mohammad; Moayedi, Ali
ABSTRACT: The functional and in vitro antioxidant properties of common kilka fish protein hydrolysates with different degree of hydrolysis (DH) obtained by kiwifruit protease (KP) and ginger protease (GP) were evaluated. The electrophoretic patterns of hydrolysates showed the presence of one major band in different DHs with a molecular weight of less than 25 kDa. Protein solubility was positively correlated with DH, and the solubility of KP and GP hydrolysates (HKP and HGP, respectively) at 15% DH was higher than other DHs ( p ≤ 0.05). Higher emulsifying and foaming properties were observed in HKP over a pH range of 2–10 ( p ≤ 0.05), and in vitro antioxidant activity was higher in HKP at 15% DH as seen from 2, 2-diphenyl-1-picrylhydrazyl radical scavenging and ferric-reducing power. Thus, the results reveal that DH and enzyme type affects functional properties and antioxidant activity of the hydrolysates.